The Relationship Between Students’ Text Genre Awareness and Critical Thinking Disposition with Their Reading Comprehension - Azizah, Hayin; F, Fahriany (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
Abstract This research was aimed at knowing the relationship among three variables, genre awareness (X1), critical thinking disposition (X2), and reading comprehension (Y). The study was conducted at SMAN 4 South Tangerang, and the participants were 180 students of the twelfth-grade students. A quantitative method was used to get through this research using the correlation as the design. Some instruments were developed to collect the data; they are tests (genre awareness test and reading comprehension test) and questionnaire to measure students’ critical thinking disposition adapted from Facione (2000). In data analysis, r product moment and R multiple regression coefficient tests was applied to test the correlation value through SPSS 21 program. The research found that (1) there is a correlation between genre awareness (X1) and reading comprehension with correlation value ro 0.876 which is higher than 0.05, (2) there is a correlation between students’ critical thinking disposition (X2) and their reading comprehension (Y) with value ro 0.263 which is higher than 0.05, (3) there is a simultaneous correlation among students’ genre awareness and critical thinking disposition with their reading comprehension with correlation value Ry.12 0.881 and the ρ-value = 0.00 < 0.05 meaning that the Ho is rejected. The contribution of X1 and X2 to support the Y variable is found as 77.5%, or it is stated that reading comprehension success is determined by students’ genre awareness and their critical thinking disposition. Abstrak Penelitian ini bertujuan mengetahui hubungan tiga variabel yaitu, pengetahuan genre (X1), sikap kritis (X2), dan kemampuan membaca (Y). Penelitian ini dilakukan di SMAN 4 Tangerang selatan dan siswa kelas XII sebagai populasi penelitian. Seluruh populasi 180 siswa dipilih sebagai sampel. Penelitian ini menggunakan metode quantitative dan model korelasi sebagai desain penelitian. Adapun untuk menjaring data, ada beberapa instrument penelitian yang digunakan yaitu tes (test pengetahuan genre dan tes pemahaman membaca) dan kuesioner sikap kritis Facione (2000). Untuk menganalisa data, penelitian ini menggunakan r product moment dan R uji koefisien regresi ganda melalui program SPSS 21. Penelitian ini membuktikan bahwa: (1) terdapat hubungan antara pemahanan genre (X1) dan pemahaman membaca siswa (Y) dengan nilai korelasi rhitung 0.876 yang mana lebih besar dari 0.05; (2) terdapat hubungan antara sikap kritis siswa (X2) dan pemahaman membaca (Y) dengan nilai indeks korelasi rhitung 0.263 yang mana lebih besar dari 0.0; (3) terdapat hubungan yang simultan di antara ketiga variable penelitian X1, X2, dan Y dengan indeks korelasi Ry.12 0.881 dan ρ-value = 0.00 < 0.05 yang menyatakan bahwa Ho ditolak. Kontribusi variable bebas terhadap variable terikat adalah sebesar 77.5%, yang manadapat dikatakan bahwa keberhasilan pemahaman membaca ditentukan oleh pengetahuan siswa terhadap genre dan sikapkrits mereka. Maka, dapat disimpulkan bahwa pengetahuan siswa terhadap genre dan sikap kritis mereka berhubungan dengan kemampuan pemahaman membaca mereka. How to Cite : Indra, H. (2017). Salafiyah Curriculum at Islamic Boarding School in the Globalization Era. TARBIYA: Journal of Education in Muslim Society, 4(1), 104-113. doi:10.15408/tjems.v4i1.5909. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i1.5909